Negative Attitudes toward U.S. Products: Malaysian Muslim Consumers' Perspective - Shah, Khairul Anuar bin Mohammad; Othman, Md Nor, Prof. Dr. (The South East Asian Journal of Management, 2008)
Consumer attitudes toward foreign products from various countries can vary significantly from one country to another. Consumer attitudes and behavioural intentions in a country can also vary overtime due to a change in the country's level of industrialization, marketing development, and lifestyle. Therefore, it is beneficial for this study to identify the attitudes of the consumers towards foreign products in a particular market. The sources of negative attitudes such as country of origin effects (Han, 1988), consumer ethnocentrism (Shimp and Sharma, 1987), and consumer animosity (Klein, Etteson, and Morries, 1998), are the factors that can influence the willingness of the consumer to purchase foreign made products. This study was gathered via survey questionnaire on the attitudes of Muslim respondents in Malaysia towards US made products. The finding suggest that animosity and ethnocentrism are negatively associated with wilingness to buy US made products.